THE ROLE OF CROSS-CULTURAL ADJUSTMENT IN BUILDING EXPATRIATE ACADEMIC RESILIENCE FOR INTERNATIONAL STUDENTS IN INDONESIA - Amol, Febriyanti; Pradana, Dominicus W; Setiawan, Didik; Amol, Apriance L. (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The aim of this research is to examine the role of academic resilience, specifically the adaptability and psychological capital capabilities of international students. This study adopts a qualitative case study, where the informants are undergraduate international students who have resided for at least three months and currently studying at a private university in Indonesia. The research indicate that psychological, sociocultural, and academic adaptation are interrelated and contribute to an individual's overall success in a new environment. These key factors cannot be implemented partially but must be approached holistically to effectively build expatriate academic resilience. Success in overcoming existing obstacles shows the importance of external and internal supporting factors in the adaptation process. This research is limited to undergraduate international students from an Indonesian private university and only includes students from one country and limited reference sources. Future research can expand the number of informants including international students from several countries. Keywords: Academic Resilience; Expatriate Academic Resilience; Adaptability Capabilities; Psychological Capital